2014
DOI: 10.1016/j.molcel.2014.08.013
|View full text |Cite
|
Sign up to set email alerts
|

c-Abl Stabilizes HDAC2 Levels by Tyrosine Phosphorylation Repressing Neuronal Gene Expression in Alzheimer’s Disease

Abstract: In Alzheimer's disease (AD), there is a decrease in neuronal gene expression induced by HDAC2 increase; however, the mechanisms involved are not fully elucidated. Here, we described how the tyrosine kinase c-Abl increases HDAC2 levels, inducing transcriptional repression of synaptic genes. Our data demonstrate that (1) in neurons, c-Abl inhibition with Imatinib prevents the AβO-induced increase in HDAC2 levels; (2) c-Abl knockdown cells show a decrease in HDAC2 levels, while c-Abl overexpression increases them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 54 publications
3
71
1
Order By: Relevance
“…HDAC2 abundance was increased in parallel with plasticity and acetylation changes in multiple AD mouse models and could be induced by amyloid b (Ab) (Fig. 1) (55,56,58). Furthermore, examination of postmortem samples from AD patients revealed that HDAC2 abundance was substantially increased even at the earliest stages of AD pathology, suggesting that HDAC2 could be a driver of cognitive decline in this disease (55).…”
Section: Hdacs In Aging and Neurodegenerative Diseasementioning
confidence: 98%
“…HDAC2 abundance was increased in parallel with plasticity and acetylation changes in multiple AD mouse models and could be induced by amyloid b (Ab) (Fig. 1) (55,56,58). Furthermore, examination of postmortem samples from AD patients revealed that HDAC2 abundance was substantially increased even at the earliest stages of AD pathology, suggesting that HDAC2 could be a driver of cognitive decline in this disease (55).…”
Section: Hdacs In Aging and Neurodegenerative Diseasementioning
confidence: 98%
“…However, a limited number of studies showed the functions of the tyrosine kinases present in the nucleus (1,2,12,14,22,53,54). Because tyrosine kinases are largely located at the plasma membrane and the cytoplasm, tyrosine phosphorylation signals have been hardly detected in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the association of AKAP8 with nuclear structures is involved in gene expression, DNA replication, and mitotic progression (26,56,57). Recently, the nuclear proteins KAT5, histone H4, and HDAC2 were reported to be tyrosinephosphorylated and to functionally associate with chromatin structures (22,54,58). Taken together, we assume that tyrosine phosphorylation of various nuclear proteins, including AKAP8, is attributable to nuclear tyrosine kinase-mediated chromatin structural changes, which could be involved in a variety of nuclear function, such as gene expression, DNA replication, and mitotic progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, what causes increases of HDAC activity in AD remains to be determined. It has been shown that amyloid β may activate c-Abl, which in turn phosphorylates HDAC 2, thereby preventing its poly-ubiquitinylation and subsequent degradation by the proteasome (85). Another identified mechanism of HDAC increase is stress.…”
Section: A Multifactorial Disease: Alzheimer's Disease (Ad)mentioning
confidence: 99%